Resisting rebellion : the history and politics of counterinsurgency - Joes, Anthony James (University Press of Kentucky, 2004)
In Resisting Rebellion, Anthony James Joes explores insurgencies ranging across five continents and spanning more than two centuries. Analyzing examples from North and South America, Europe, Africa, and the Middle East, he identifies recurrent patterns and offers useful lessons for future policymakers. Insurgencies arise from many sources of discontent, including foreign occupation, fraudulent elections, and religious persecution, but they also stem from ethnic hostilities, the aspirations of would-be elites, and traditions of political violence. Because insurgency is as much a political pheno.